Leading the Unwilling: Unilateral Strategies to Prevent Arctic Oil Exploration - Leroux, Justin; Spiro, Daniel (Munich: Center for Economic Studies and ifo Institute (CESifo), 2017)
Arctic oil extraction is inconsistent with the 2°C target. We study unilateral strategies by climate-concerned Arctic countries to deter extraction by others. Contradicting common theoretical assumptions about climate-change mitigation, our setting is one where countries may fundamentally disagree about whether mitigation by others is beneficial. Arctic extraction requires specific R&D, hence entry by one country expands the extraction-technology market, decreasing costs for others. Less environmentally-concerned countries (preferring maximum entry) have a first-mover advantage but, being reliant on entry by others, can be deterred if environmentally-concerned countries (preferring no entry) credibly coordinate on not following. Furthermore, using a pooling strategy, an environmentally-concerned country can deter entry by credibly "pretending" to be environmentally adamant, thus expected to not follow. A rough calibration, accounting for recent developments in U.S. politics, suggests a country like Norway, or prospects of a green future U.S. administration, could be pivotal in determining whether the Arctic will be explored.